Bilingual Education Current Perspectives. Volume 1.: Social Science - Fishman, Joshua A.; Center for Applied Linguistics, Arlington, VA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
Recognizing a need for an objective, multidisciplinary and comprehensive look at the field of bilingual education, the Office of the Commonwealth of Puerto Rico and the Center for Applied Linguistics cooperated in a state-of-the-art study of the field. State-of-the-art papers were commissioned in four general areas concerning bilingual education: social science, languages and linguistics, law, and education. Each paper formed the central focus for a separate conference at which it was discussed and elaborated upon by specialists from various fields within a given discipline. This volume is the first in a series of four volumes that present a collection of the major papers and the viewpoints of the discussants. The focus of the volume is social science. The state-of-the-art paper is "The Social Science Perspective," by Joshua Fishman, and the viewpoints include: "Social History," by Shirley Brice Heath; "Ethongraphy," by Hugh Mehan; "Anthropology," by Sarah Nieves-Squires; "Sociology and Education," by H. Ned Seelye; and "Political Science," by Brian Weinstein. A bibliography concludes the volume. (CLK)
Availability: Center for Applied Linguistics, 1611 N. Kent St., Arlington, Virginia 22209 ($7.95 plus $1.50 postage and handling for orders under $10.00).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Anthropology; Bilingual Education; Bilingual Students; Bilingualism; Educational Policy; Ethnography; Language Instruction; Language of Instruction; Language Planning; Political Science; Second Language Learning; Social History; Social Science Research; Social Sciences; Sociology; State of the Art Reviews; Reports, Research